(untitled) (Doctor Virtualis, 2022)
This paper investigates the Jewish moral law’s foundation according with teaching of Samuel David Luzzatto (1800-1865). He affirms that ethical norms come from human being, but this is not enough for them to be respected: therefore divine revelation supports natural morality, teaching the same, but providing adequate preparation and providing penalties and rewards. Only monotheism, with its necessary worships, can therefore found an effective morality. It appears essentially in humanity and justice towards all human beings.